Epigenetics and In Utero Acquired Predisposition to Metabolic Disease - Deodati, Annalisa; Inzaghi, Elena; Cianfarani, Stefano (Frontiers in Genetics, 2020)
Epidemiological evidences have revealed an association between prenatal malnutrition and a greater risk of developing metabolic disease in later life. Indeed, an inadequate intrauterine milieu may influence both growth and development of the organism, leading to permanent programming of endocrine and metabolic functions. Programming may be due to the epigenetic modification of genes implicated in the regulation of key metabolic mechanisms, including DNA methylation, histone modifications and miRNAs. microRNA (miRNA) expression in critical organs for metabolism resulted influenced by programming in utero, as demonstrated by experimental and human studies. miRNAs modulate multiple pathways such as insulin signaling, immune system, adipokine function, lipid metabolism, and food intake. Multiple evidences support that liver is a one of the programmed organs, undergoing structural, functional and epigenetic changes following exposure to suboptimal intrauterine environment. The focus of this review is to show an overview of the evidence of the effects on epigenome of exposure to adverse in utero mileu with focus on the molecular mechanisms involved in liver programming.